Breastfeeding self-efficacy as a dominant factor affecting maternal breastfeeding satisfaction - Siti Nurbayanti Awaliyah; Imami Nur Rachmawati; Hayuni Rahmah (BMC, 2019)
Abstract Background One of the psychological benefits of breastfeeding for mothers and infants is to get the satisfaction of breastfeeding. Maternal breastfeeding satisfaction derives from the interaction and cooperation between mothers and their babies. This research aims to identify the maternal breastfeeding satisfaction and its influential factors. Methods This study applied a cross-sectional design. Two hundred four breastfeeding mothers after four until 8 months postpartum were recruited using cluster sampling methods. Respondents completed the questionnaire of Maternal Breastfeeding Evaluation Scale (MBES) to identify maternal breastfeeding satisfaction. Factors affecting maternal breastfeeding satisfaction were identified using the following instruments: Breastfeeding Knowledge Questionnaire was used to identify knowledge on lactation, Infant Feeding Attitude Scale (IIFAS) to identify attitude toward lactation, and the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) to identify breastfeeding self-efficacy. Result We identified that 53.4% of the breastfeeding mothers had a high level of satisfaction. The results indicate that the household income, type of delivery, and breastfeeding self-efficacy was associated with breastfeeding satisfaction (p < 0.05). Breastfeeding self-efficacy is the most influential factors in maternal breastfeeding satisfaction (OR=16.64; CI 95% 7.65-35.94). Conclusion Breastfeeding satisfaction is the satisfying feeling obtained during breastfeeding resulting from cooperation between the mother and the infant to fullfil desires or needs. Education and promotion of breast milk and breastfeeding provided by professional healthcare providers encouraged the successful of breastfeeding programs. Assistance by a health care provider or breastfeeding counselor during the seven contacts breastfeeding initiated during pregnancy until after delivery should be applied so that the mother is informed about breastfeeding. Breastfeeding satisfaction can keep the mother from continuing to breastfeed her baby for up to 2 years or more.